Research progress in iron biomarkers: a review - Wenfei PAN; Kunkun TU; Xiaojie MA; Min YANG (Editorial Office of Chinese Journal of Public Health, 2024)
Iron is essential in various life processes, and its imbalance is closely related to disorders in multiple systems such as the nervous, cardiovascular, and immune systems, as well as many chronic diseases such as infections and cancer. Therefore, accurately assessing the status of iron in the body is of great significance for both basic and clinical research. The gold standard for iron status is still bone marrow stainable iron, but its actual application is very limited due to its invasive sampling and high cost. Other traditional biomarkers such as serum iron, ferritin, and related composite indicators are all affected to varying degrees by factors such as inflammation, age, and circadian fluctuations, but they also have their own suitable application scenarios. However, biomarkers that can fully assess iron status are far from perfect, leading to inaccurate diagnosis and treatment of iron imbalance in many cases. Although new biomarkers such as hepcidin, reticulocyte hemoglobin content, and erythroferrone have emerged, and with the rapid advancement of high-throughput technologies, multi-omics may help diagnose iron status in the future, more exploration and mining are still needed to expand the widespread and rational application of these potential markers. This article reviews the research progress of iron biomarkers, aiming to provide more references and directions for future related research.